PEMBELAJARAN MATERI ELASTISITAS DAN HUKUM HOOKE DENGAN MODEL PEMBELAJARAN GUIDED DISCOVERY DI SMA NEGERI 1 JENGGAWAH - yayan mega lusiana; yushardi yushardi; sudarti sudarti (FKIP Universitas Jember, 2017)
The aim of this research is to study the effect of guided discovery learning model on critical thinking skills and motivation of students on learning materials elasticity and Hooke law. Learning physics in the classroom tends to be monotonous and less attractive where students are not involved directly in the find a concept, so that the students have not been motivated to active in learning. The effect critical thinking skills of students is low, because students did not experience their own facts that happened. This research is an experimental research. This research was conducted at SMAN 1 Jenggawah. The data are collected by test, questionnaire, interview, and documentation. To examine the hypothesis, this research used independent sample t-test with SPSS 22 version. According to independent sample t-test analysis in the critical thinking skills showed sig value (2-tailed) is 0,000 or < 0,05 then Ho is rejected, and for the motivation of student’s showed sig value (2-tailed) is 0,000 or < 0,05 then Ho is rejected. In conclusion, the guided discovery learning model has a significance influential to critical thinking skills and motivation of students on learning materials elasticity and Hooke law in Senior High School 1 Jenggawah